Equity valuation of CTT: an analysis before and after the IPO - Domingos, Ana Rita Fontinha da Silva (2016)
CTT – Correios de Portugal S.A. is one of the most important companies in Portugal. With the recent privatization, people fear that the company has been sold only to meet a specific need of cash by the Portuguese Government and that the public service may be affected. It is in this context that arises the need to evaluate the company in order to verify if the sale price was a fair price for both parts in the deal. To do this evaluation it will be applied the most used approaches by financial analysts such as Discounted Cash Flow models and Multiples approach. In addition, it will be analyzed the value of the company one year later to its sale and verify if the company appreciated or devalued with its entry on the stock market. With this result, a recommendation will be given to investors for the attitude that must be taken into account about the possible future behavior of the share price in the market.